FAKTOR-FAKTOR PENDAPATAN TENAGA KERJA USAHATANI JAMBU KRISTAL (PSIDIUM GUAJAVA L) (STUDI KASUS) PAPANY FARM DI KECAMATAN CEMPAKA KABUPATEN OGAN KOMERING ULU TIMUR - Nasrullah teguh; yetty oktarina; ema pusvita (JASEP, 2022)
This research was conducted in Cempaka Subdistrict, Ogan Komering Ulu Timur Regency on January 28, 2021. The method used in this study is a case study method, by examining in depth the income of the papany farm guava crystal farming in Cempaka District, Ogan Komering Ulu Timur Regency. This study aims to analyze the factors of labor income in the cultivation of guava crystal (Psidium Guajava L) Papany Farm (Case Study) in Cempaka District, Ogan Komering Ulu Timur Regency. The method used in this study is saturated sampling. Saturated sampling method is a sampling technique when all members of the population are used as samples. This method is used when the population is relatively small, less than 30 people. The sample in this study is the total number of workers in the Papany Farm guava crystal, totaling 15 people. Factors that affect labor income, namely: length of work and hours of work people have an effect on the income of the keristal guava farm worker, as evidenced by the positive and very significant influence of the variable length of work (0.131) hours of work (0.260) and type of work. There is no positive effect on labor income because the value of the type of work (-0.069) with the F test (comprehensive test) on income. The determination test (R2) of variable income, length of work, hours of work, and type of work is 70.2%, while the remaining 29.8% is influenced by other variables which are not discussed in this study.Keywords: labor factors, crystal guava farming, case studies